Length of online course and student satisfaction, perceived learning, and academic performance - Janet M. Ferguson (Athabasca University Press, 2010)
This research presents findings from a two-part study. In the first part, graduate students taking online courses were given a course evaluation form. Student responses from online abbreviated summer sessions were compared to student responses from online full-semester courses.